GREEN TOURISM CONCEPT: STRENGTHENING MSMES THROUGH BUSINESS DIGITALISATION AND SUSTAINABLE TOURISM IN JENGGLUNGHARJO VILLAGE - Anugrahani, Inanda Shinta; Purnamasari, Fitri; Muhammad, Muhammad (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service programme aims to improve the welfare of the people of Jengglungharjo Village through strengthening MSMEs based on business digitalisation and sustainable tourism. This activity is carried out through a series of training, mentoring, and preliminary surveys involving various stakeholders, namely MSME players, the Village Government, and BUMDes (Village-Owned Enterprises). The main focus of the programme is to equip the community with digital skills to optimise local product marketing and promote village tourism potential. One of the main outputs of the programme is the development of a tourism village website, visitjengglungharjo.id, which not only provides tourism information but is also equipped with e-commerce features to market local products. The results of this implementation show an increase in community understanding in utilising digital technology, an increase in MSME product transactions through online platforms, as well as an increase in tourist visits. This programme proves that digitalisation can be an effective solution to expand the market reach of MSMEs while supporting sustainable tourism in rural areas